Physicochemical and fatty acid profile of egusi oil from supercritical carbon dioxide extraction - O. Olubi; J.V. Felix-Minnaar; V.A. Jideani (Heliyon, 2019)
Oil extraction from egusi seeds using supercritical CO2 extraction method was performed using series of operational parameters, temperature (55, 60, 75 °C), flow rate (30 g/h) and pressure (450, 600 bar). Egusi oil (EO) extracted at 60 °C, 30 g/h and 450 bar (EO1); 55 °C, 30 g/h and 600 bar (EO2) and 75 °C, 30 g/h and 600 bar (EO3) were investigated in a plant scale supercritical equipment. The fatty acid composition of egusi oil was analysed using gas chromatography, with result showing a high linoleic acid approximately (53%) and oleic acids (19%). The index of atherogenicity (IA%) and thrombogenicity index (IT %) were significantly low for the three oil samples, indicating its health benefits. Oxidative stability of egusi oil was analysed by Methrohm 743 Rancimat, confirming a less oxidised oil. Hence, egusi oil can be used as a raw material in dietary supplements and as a functional oil in the food industry.